2021
DOI: 10.1111/iju.14731
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival variations of upper tract urothelial cancer in Taiwan (2001–2010)

Abstract: Objectives To assess temporal patterns and regional differences in the incidence rate, and factors associated with survival of urinary tract urothelial carcinoma. Methods The medical records of 8830 patients with new diagnoses of urinary tract urothelial carcinoma in the years 2001–2010 were retrieved from Taiwan National databases. Temporal trends, regional disparity and related survival factors were evaluated using the Cochran–Armitage trend test, local Moran’s I statistic and log‐rank test, respectively. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Seven clusters of urbanization stratification were grouped into four levels: high, medium–high, medium, and low urbanization, according to the previously published consensus methodology 45 . Clusters of high bladder cancer incidence rate in the black-foot disease endemic regions included six southwestern coastal townships where people unknowingly drank arsenic-contaminated well water before tap water installation in 1979–2003 46 48 . The study subjects originating from these regions were identified and regarded as a confounder for adjustment in the multivariate Cox models.…”
Section: Methodsmentioning
confidence: 99%
“…Seven clusters of urbanization stratification were grouped into four levels: high, medium–high, medium, and low urbanization, according to the previously published consensus methodology 45 . Clusters of high bladder cancer incidence rate in the black-foot disease endemic regions included six southwestern coastal townships where people unknowingly drank arsenic-contaminated well water before tap water installation in 1979–2003 46 48 . The study subjects originating from these regions were identified and regarded as a confounder for adjustment in the multivariate Cox models.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that there are sex‐specific differences in UTUC, with the prevalence of UTUC being approximately twice as high in males than in females in the United States and Western European 7,10,11 . In contrast, a 2001–2010 Taiwanese study showed that the annual incidence of UTUC in women was significantly higher than that in men (female to male ratio: 2.08–3.25) 9 . Relevant studies conducted in recent years have determined that the carcinogenic mechanisms of UTUC are related to smoking, exposure to aristolochic acid, genetic predisposition, and environmental factors 12,13 .…”
Section: Introductionmentioning
confidence: 97%
“…However, compared with those in other countries, the incidence of upper tract urothelial cancer (UTUC) in Taiwan is abnormally high, especially in women 2–6 . The annual incidence of UTUC is 1–2 cases per 100,000 people worldwide, but it is 3.14–3.41 in Taiwan 7–9 . Previous studies have shown that there are sex‐specific differences in UTUC, with the prevalence of UTUC being approximately twice as high in males than in females in the United States and Western European 7,10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Another relatively rare type of UC called upper tract urothelial carcinoma (UTUC) that accounts for 5%-10% of UC is located in the renal pelvis and ureter (3). The annual incidence of UTUC ranges from 1.2 to 4.7 cases per 100,000 inhabitants and also frequently occurs in men globally (4). In contrast, UTUC has an unusually high incidence that accounts for 40% of UC in Taiwan (5).…”
Section: Introductionmentioning
confidence: 99%